Biallelic loss‐of‐function mutations in SEPTIN4 (C17ORF47), encoding a conserved annulus protein, cause thin midpiece spermatozoa and male infertility in humans. Issue 12 (2nd October 2022) - Wang, Guanxiong; Zhu, Xiaoyu; Gao, Yang; Lv, Mingrong; Li, Kuokuo; Tang, Dongdong; Wu, Huan; Xu, Chuan; Geng, Hao; Shen, Qunshan; Zha, Xiaomin; Duan, Zongliu; et al.
Abstract: Asthenoteratozoospermia is the primary cause of infertility in humans. However, the genetic etiology remains largely unknown for those suffering from severe asthenoteratozoospermia caused by thin midpiece defects. In this study, we identified two biallelic loss‐of‐function variants of SEPTIN4 (previously SEPT4) (Patient 1: c.A721T, p.R241* and Patient 2: c.C205T, p.R69*) in two unrelated individuals from two consanguineous Chinese families. SEPT4 is a conserved annulus protein that is critical for male fertility and the structural integrity of the sperm midpiece in mice. SEPT4 mutations disrupted the formation of SEPT‐based annulus and localization of SEPTIN subunits in sperms from patients. The ultrastructural analysis demonstrated striking thin midpiece spermatozoa defects owing to annulus loss and disorganized mitochondrial sheath. Immunofluorescence and immunoblotting analyses of the mitochondrial sheath proteins TOMM20 and HSP60 further indicated that the distribution and abundance of mitochondria were impaired in men harboring biallelic SEPT4 variants. Additionally, we found that the precise localization of SLC26A8, a testis‐specific anion transporter that colocalizes with SEPT4 at the sperm annulus, was missing without SEPT4. Moreover, the patient achieved a good pregnancy outcome following intracytoplasmic sperm injection. Overall, our study demonstrated for the first time that SEPT4 variants that induced thin midpiece spermatozoa defects were directly associated with human asthenoteratozoospermia.